STRATEGY TO CONVALESCE CUSTOMER SATISFACTION FOR SELLING HYDROPONIC VEGETABLE DURING THE PANDEMIC OF COVID-19 - Rivan Sutrisno; Gundur Leo (Journal of Management, Business and Social Sciences, 2023)
This study aims to find out whether there is an influence of the marketing mix 4P's on Halethponic.id customer satisfaction. The population in this study are customers from Halethponic.id and there are 50 people as samples. The method used is the Multiple Linear Regression analysis method with a descriptive quantitative approach. Based on the results of the study it is known that the marketing mix 4P's (price, product, place, promotion) simultaneously has a positive and significant influence on customer satisfaction. The suggestions obtained from this study are that Halethponic.id can maintain a stable marketing mix that is good for customers, create a characteristic, pay attention to prices, promote products through advertisements, consider places and improve services so that they can maintain customer satisfaction.